(untitled) (Biocenosis, 2022)
Human observations of the Amazona auropalliata (yellow-naped amazon) and Quiscalus mexicanus (zanate) were analyzed in the Costa Rican territory, the area of ​​interest, where the geographic distribution pattern and its influence on the niche overlap of both species were known. Twenty bioclimatic variables were used, using the RStudio program where the main variable correlations were known for each of the species in this study. The invasive species, being Quiscalus mexicanus, has a wide expansion of geographical distribution since it can adapt to areas of great disturbance caused by human beings such as: urbanization or agricultural activities, it also tolerates climatic changes, while Amazona auropalliata has a restricted distribution according to their feeding and nesting. Consequently, it can be predicted that the invasive species could influence the reduction of the populations of Amazona auropalliata which is in danger of extinction according to IUCN (2020).